CC-chemokine receptors: a potential therapeutic target for Trypanosoma cruzi-elicited myocarditis - Marino, A. P. M. P. (2005)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Imunologia. Laboratório de Autoimunidade e Imuno-regulação. Rio de Janeiro, RJ, Brasil.